Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

rannsan

  • 3 years ago

Find the solution to this system using the substitution method. 2x -5y = -1 and x -3y = -3

  • This Question is Closed
  1. mathslover
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    2x-5y = -1 2x = -1 + 5y x = \(\large{\frac{-1+5y}{2}}\)

  2. mathslover
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    put this value in the second eqn : \[\large{x-3y=-3}\] \[\large{\frac{-1+5y}{2}-3y=-3}\]

  3. matricked
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    form the second equation we have x=3y -3 putting it in the first we have 2(3y-3)-5y=-1 or 6y -6-5y =-1 or y=6-1 or y=5 hence x=3(5) -3=12 x=12 and y=5

  4. mathslover
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    \[\large{\frac{-1+5y-6y}{2}=-3}\] \[\large{-1-y=-6}\] \[\large{-1+6=y}\] \[\large{5=y}\]

  5. chemENGINEER
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    its too sticky and icky...mmmmmm

  6. mathslover
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    similarly find x x- 3(5) = -3 x-15=-3 x = -3+15

  7. mathslover
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    got it @rannsan ?

  8. rannsan
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    I think so

  9. rannsan
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thank you!!

  10. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy